Developing and Testing Digital Book Media to Enhance Reading Literacy in Blended Elementary Learning: An ADDIE-Based Experimental Study - Putri, Ragil Dian Purnama; Nugraheni, Anindiya Sri; Zakiya, Faza (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading literacy is a basic competence that must be mastered by elementary school students; however, students’ reading literacy in Indonesia remains relatively low due to limited literacy facilities, suboptimal teacher roles, and the lack of literacy media aligned with student characteristics in blended learning. This study aimed to develop digital book–based literacy media and examine its feasibility and effectiveness in improving the reading literacy of third-grade elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of needs analysis at Pilangrejo and Natah Elementary Schools, media design and development using Flip PDF Corporate Edition, validation by media and content experts, and implementation in an experimental class. The results showed that the digital book media was categorized as very feasible based on evaluations by media experts with a score of 57 (95), material experts with a score of 60 (100), and third-grade teachers with a score of 54 (90). Effectiveness testing indicated a significant improvement in students’ reading literacy, as evidenced by the t-test results in the experimental class (t = 2.787 > t-table = 2.037), while the control class showed no significant difference (t = 1.413 < t-table = 2.145). These findings demonstrate that digital book–based literacy media is effective in increasing elementary school students’ reading literacy in blended learning.